An improvement of voltage quality in low voltage distribution system using dynamic voltage restorer - Bukar, Abba Lawan (2015)
With the increased use of semiconductor devices (switched mode power supply) and ICT (information communication technology) equipment in homes, offices and the industry, power quality (PQ) is gaining significant interest to both the electric utility and the industry. The absence of power quality causes enormous economic losses all over the world; it is estimated that PQ problems cost commerce and industry about 100 billion Euros per annum in the European Union. One of the most and undesirable PQ phenomenon are voltage sags, which puts sensitive loads under risk. This project is therefore, aimed at mitigation of power quality problems such as voltage sag, voltage swell, interruption and harmonic at low voltage distribution system, using a versatile custom power device that is capable of mitigating various types of PQ disturbances called dynamic voltage restorer (DVR). Implementations of DVR have been proposed at both a medium and low voltage levels to protect sensitive loads from power quality problems. The proposed system is designed using Matlab/Simulink SimPower System Tools Box. The proposed DVR system comprises of line filter, voltage injection transformer, voltage source inverter, bypass switch and energy storage device from which the power necessary for compensation can be obtained during PQ disturbance. Simulation results verified the capability of the proposed DVR system in mitigating the power quality problems in a low-voltage distribution system.